Belongingness and Distinctiveness: The Compensating Effects of Personal Resources - Law-Penrose, Jared; Couto, Tracy (Journal of Organizational Psychology, 2023)
This research examines the relationships between the satisfaction of psychological needs (belongingness and distinctiveness) on affective and cognitive attitudes (job satisfaction and commitment). Specifically, this study evaluates how the satisfaction of one psychological need compensates for the lack of the other psychological need. Overall this study found that the satisfaction of one psychological need can, in certain circumstances, compensate for the lack of satisfaction of a different psychological need. Results and implications are presented through the JDR framework. This study offers an important extension of the JDR by incorporating personal resources as key predictors of job outcomes. Practical implications are discussed for EAP professionals/counselors.